Impact of cane use on pain, function, general health and energy expenditure during gait in patients with knee osteoarthritis: a randomised controlled trial. Issue 2 (29th November 2011) - Jones, A; Silva, P G; Silva, A C; Colucci, M; Tuffanin, A; Jardim, J R; Natour, J
Abstract : Objective: To assess the impact of daily cane use during gait in relation to pain, function, general health and energy expenditure among patients with knee osteoarthritis. Method: Sixty-four patients were randomly assigned to an experimental group (EG) or control group (CG). The EG used a cane every day for 2 months, whereas the CG did not use a cane in this period. The first outcome was pain and the second were function (Lequesne and WOMAC), general health (SF-36) and energy expenditure (gas analysis during the 6-minute walk test (6MWT) with and without a cane). Evaluations were performed at baseline, 30 and 60 days. Results: The groups were homogeneous for all parameters at baseline. Compared with the CG, the EG significantly improved pain (ES 0.18), function - Lequesne (ES 0.13), some domains of SF-36 (role physical, ES 0.07 and bodily pain, ES 0.08) and distance on the 6MWT with the cane (ES 0.16). At the end of the 6MWT with the cane, the EG significantly improved energy expenditure (ES 0.21), carbon dioxide production (ES 0.12) and metabolic equivalents (ES 0.15) compared with the CG. Conclusion: A cane can be used to diminish pain, improve function and some aspects of quality of life in patients with knee osteoarthritis. The prescription of a cane should take into account the substantial increase in energy expenditure in the first month of use, whereas energy expenditure is no longer a factor for concern by the end of the second month due to adaptation to cane use. The trial was registered in clinicaltrials.gov (NCT00698412 ).